ANALISIS TEGANGAN STATIK DAN DEFORMASI FRAME ELECTRIC GANESHA SCOOTER PORTABLE (E-GASPOL) MENGGUNAKAN SOFTWARE SOLIDWORKS - I Gede Wiratmaja; Nyoman Arya Wigraha; Komang Purnayasa (Otopro, 2023)
This study aims to determine and reduce static stress and increase the safety factor on the E-GASPOL vehicle frame. The type of development research used is the R2D2 type (Reflective, Recursive, Design and Development) which has three phases, namely defining, design and development and dissemination. The data analysis technique used is the finite element method, this method can solve static, dynamic, linear and non-linear problems. In this study, the static stress analysis of vehicle frame was carried out in conditions without rider load (the mass of the frame itself is 13.34 kg) and conditions with rider load (frame mass of 13.34 kg + average rider mass of 70 kg, so the total is 83.34 kg). The static stress analysis results on the four designs, the results of the modified vehicle frame design 3 have the best value, namely obtaining a maximum stress value of 1,255xN/m conditions without rider load, this result gets a decrease of 58.55% from the standard design and with a rider load of 7,699xN/m, this result gets a decrease of 58.56% from the standard design, the smaller the stress value obtained on a frame. The maximum displacement/deformation value of 1,453xmm conditions without rider load, this result gets a decrease of 77.718% from the standard design and with a rider load of 8,791xmm, this result gets a decrease of 78.10% from the standard design. From the data it can be concluded that the modified frame is better and stronger than the standard frame.